‘If I Wanted to Have More Opportunities and Go to a Better School, I Just Had to Get Used to It’: Aboriginal Students’ Perceptions of Going to Boarding School in Western Australia - Mander, David J.; Cohen, Lynne; Pooley, Julie Ann (The Australian Journal of Indigenous Education, 2015)
This study explored the experiences of 32 male Aboriginal students from regional and remote towns and communities while they attended a metropolitan boarding school away from home and family in Perth, Western Australia. Using narrative interviews it specifically investigated how these Aboriginal students construct meaning around the transition experience to boarding school. Three major themes emerged from the data: (1) Decision Making and the subthemes of Choice-less Choice and Opportunity; (2) Organisational Climate and the subthemes of School Environment and Belonging, Culture Shock, Homesickness, Identity, Code Switching, Teachers, Academic Expectations, Residential Life, and Friendships and Peer Relations; and (3) Relational Change and the subthemes of Family Dynamics, Friendships at Home, and Cultural Connectedness. This study emphasises the importance of conceptualising and understanding social phenomena from the perspective of those who actually undertake the experience, and the findings are discussed in terms of policy and practice relevant to Australian boarding schools.